Project Tango: Building a team, laying ground rules and managing communications with stakeholders. Issue 2 (November 2020) - Hassandoust, Farkhondeh; Díaz Andrade, Antonio
Project management is a mix of both science and art. It is a science because project managers need to estimate and manage time and cost. It is an art because they should ensure that all team members are in sync, while stakeholders are efficiently projecting the point across without communication gaps. It has been long recognised that developing nontechnical (i.e. 'soft') skills of project managers and team members plays a critical role in the success of any project regardless of industry. Such skills reflect the leadership skills of project managers, which typically fall under the knowledge areas of project resource management, project communications management and project stakeholder management. Even though there are many strategies for improving soft skills in a project team, the challenges in implementing these strategies are not often discussed. Recognition of the significance of these aspects is not novel, yet most project management studies are focused on the technical (i.e. 'hard') skills of project management. This teaching case aims to bridge this gap by inviting students to reflect on how soft skills can make a difference throughout the project lifecycle. The case is about a mobile telecommunication network upgrade project in New Zealand. Despite being completed on time, on budget and at the agreed scope, the project was never implemented due to the acquisition of the client by a larger telecommunications company, which had other strategic priorities. The focus of the teaching case is on leadership skills and communication management in projects.